Transformações geométricas e matrizes: uma proposta de ensino com base na sala de aula invertida - Zanchettin, Luciana (2020)
The objective of this work is to present a teaching proposal through a didactic sequence on the study of geometric transformations and their representation through matrices. For this, we adopted the active methodology called Inverted Classroom and divided the didactic sequence into individual learning and virtual spaces offered by the Khan Academy platform and the GeoGebra software and in groups in the classroom mode. The study planned to be developed in six meetings includes activities on reflection, translation, rotation and scale transformation and their relations with matrices. The activities of the didactic sequence were elaborated taking into account the three moments of the Inverted Classroom: Pre-class, Class and Post-class and besides the mathematical concepts to be treated, students will be challenged to indicate situations that can be solved with the use of knowledge acquired on the geometry of transformations. The work was carried out through a bibliographic research of the documentary study type based on textbooks of Mathematics of High school and Higher Education, scientific articles and access to the Khan Academy platform and the GeoGebra software. We believe that this proposal can favor the teaching and learning process and contribute to the development of students' autonomy and creativity, contemplating the studied themes and contributing to the solution of some social problem in the community or in the school environment.